Breastfeeding practices and head circumference in young children: a systematic review - Isabel Giacomini; Lucas Damasio Faggiani; Paola Soledad Mosquera; Marly Augusto Cardoso (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To review observational studies on the association between breastfeeding (BF) practices and head circumference (HC) of children < 2 years old. METHODS A systematic review was conducted using the following electronic databases of health sciences: PubMed, Latin American and Caribbean Literature in Health Sciences (Lilacs), Web of Science and Scopus. We selected observational studies published in any language from January 01, 2010 to November 19, 2021, from different populations that investigated the association between BF practice and HC among healthy children < 2 years old. Titles and abstracts were screened independently by two evaluators. RESULTS From the 4,229 articles identified, 24 were included in this review: 6 cross-sectional, 17 longitudinal, and 1 case-control. The studies varied in their definition of the variables for BF and in reporting its practice, frequency, duration, and feeding method. Regarding HC, the authors analyzed the mean differences, abnormal values (z-score above + 2SD or below -2SD according to the World Health Organization (WHO) growth standards, 2007), and longitudinal growth parameters. The findings of this review suggest that BF may have a positive relationship with HC at the beginning of life. CONCLUSIONS Our findings suggest that BF, especially exclusive BF, may play a protective role against abnormal HC values in young children. However, more robust evidence with standardized BF indicators and WHO growth standards (2007) are required.